Arabic calligraphy and writing throughout history - betta, merzoug; hrouz, abdelghani (The Algerian Historical Journal, 2026)
Man tried since ancient times to express his thoughts and what is going on in his mind, and he used in these attempts to different methods, which he started using pictures and drawings, then these means developed with the development of man, and his telegram rose to finally reach the use of the written language and then the languages ​​multiplied and differed. From one place to another, letters were used in writing the language, and people of different languages ​​mastered the writing of letters, and the art of calligraphy emerged from that, which people counted as a fine art, and among the calligraphy is Arabic calligraphy. The Arabic calligraphy has a special symbolism in the Arab-Islamic civilization, as it expresses the identity of the Islamic nation associated with science and writing, and that is validated by the words of the Blessed and Almighty in a tightly downloaded: Read in the name of your Lord who created (1) He created the most gracious man from a clothe (2) (3) The one who taught with the pen (4) taught man what he did not know (5) 1, and with what reflects it in terms of historical depth and what it contains in an artistic sense and what nourishes him from aesthetic taste, and besides all this, Arabic calligraphy is considered in terms of development and from the technical point of view, The world's most diverse, flexible and aesthetically pleasing lines, with the unlimited ability to develop, and this is what has been proven by the historical periods across their various different periods.